THE EVALUATION OF A SMOKE-FREE AREA DECLARATION PROGRAM TO CREATE A HEALTHY CITY AT PUSKESMAS GONDOKUSUMAN - Desi Nurfita; Rokhmayanti Rokhmayanti; Helfi Agustin; Sandheep Sugathan (Epidemiology and Society Health Review (ESHR), 2019)
Background: Indonesia is experiencing a major health challenge, that is triple burden diseases (communicable diseases, non-communicable diseases, and reemerging diseases). One of the programs established by the government to face the threat is Healthy Lifestyle Community Movement (Gerakan Masyarakat Hidup Sehat or GERMAS). The declaration of the smoke-free area is one of the efforts of the Government on this movement aimed to have smoke-free homes to create a healthy city. However, the monitoring and evaluation of the program do not run well. The goal of this research is to provide a description and analysis of the implementation of the smoke-free area declaration program.Methods: This was qualitative research. The subjects or main informants of this study were the people in charge of the smoke-free area declaration program and the head of the clinic at Puskesmas Gondokusuman 2. The supporting informants in this study were the community declaring the program as well as the elite figures of the community involved in the declaration. The method of primary data collection was through in-depth interviews, observation, and review documentation. The implemented analysis technique was content analysis.Results: The inputs of the smoke-free area declaration program were measured from the human resources, fund, facilities, organization, information, and guidelines. Further, the process of the smoke-free area declaration was viewed from the community roles, community responses, and reports. However, there was a shortcoming of the process variable, i.e. the in-existence of written reports done by the head of the program. Furthermore, the output variables were observed from the commitments, impacts on society, and the comprehensiveness of the reports. Conclusions: Based on the analysis, the inputs of the program were considered as well. The outputs of the program were considered to be positive.